Contact Region Estimation Based on a Vision-Based Tactile Sensor Using a Deformable Touchpad - Ito, Yuji (MDPI, 2014)
A new method is proposed to estimate the contact region between a sensor and an object using a deformable tactile sensor. The sensor consists of a charge-coupled device (CCD) camera, light-emitting diode (LED) lights and a deformable touchpad. The sensor can obtain a variety of tactile information, such as the contact region, multi-axis contact force, slippage, shape, position and orientation of an object in contact with the touchpad. The proposed method is based on the movements of dots printed on the surface of the touchpad and classifies the contact state of dots into three types—A non-contacting dot, a sticking dot and a slipping dot. Considering the movements of the dots with noise and errors, equations are formulated to discriminate between the contacting dots and the non-contacting dots. A set of the contacting dots discriminated by the formulated equations can construct the contact region. Next, a method is developed to detect the dots in images of the surface of the touchpad captured by the CCD camera. A method to assign numbers to dots for calculating the displacements of the dots is also proposed. Finally, the proposed methods are validated by experimental results.